A study on perceived stress among undergraduates during the MCO at Universiti Kebangsaan Malaysia (UKM) / Fatin Nuraisyah Suffian and Nur Aqilah Kamarulzaman - Suffian, Fatin Nuraisyah (2022)
The purpose of this study is to examine whether there is a relationship between multiple determinants and perceived stress level among undergraduates in Universiti Kebangsaan Malaysia (UKM). The determinants include demographic information, residential condition, online distance learning (ODL) and internet access. The main intention of this study is to find the primary determinants that influence the perceived stress level among undergraduates in UKM. The study involves cross-sectional and descriptive study where researchers use online surveys as the primary data collection tool. The respondents come from 341 undergraduates of UKM using a convenience sampling technique. Mean was used to measure the perceived stress level among undergraduates in UKM. Meanwhile, regression and correlation analysis were used to identify the relationship between a dependent variable and independent variables. The study did not give solid evidence of the relationship between determinants that influence the perceived stress level among undergraduates in UKM. Hence, it is suggested for future researchers to focus on a large scope of determinants that might influence perceived stress level among undergraduates nationwide.